Plasma Characterization of Microwave Plasma jet at Atmospheric Pressure - Abdulwahab, Hiba M.; Humud, Hammad R. (Iraqi Journal of Science, 2024)
The microwave induced plasma jet (MIPJ) system was built using local materials and based on a tapered waveguide. The parameters of this plasma were determined like electron temperature Te, electron density ne. the other parameters such as plasma frequency( fp), the Debye length( λD), and the number of particles in the Debye sphere( Nd) It has also been studied. The study were done at different Ar flow rate ranging from (2-10) l/m and a discharge tube diameter ranging from (2-10) mm. all of these parameters were determined depending on the MIPJ spectrum. it turned out that there is a high possibility of controlling the parameters of MIPJ through manipulating these parameters.